Strategi Bisnis Restoran Vegetarian Bite N Chat Pada Kondisi Pandemi Covid 19 dalam Meningkatkan Pasar Konsumen - Addristy Chandra Madani; Nia Rosiana (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2022)
Public awareness of healthy living is growing in Indonesia. Being a vegetarian is one of the people's choices in implementing a healthy lifestyle. One of the vegetarian restaurants currently established is Bite n Chat which is in a competitive environment in the culinary field in North Jakarta. The Bite n Chat Restaurant experienced a 8.9 percent decrease of revenue during January to September 2020. The purpose of the study is to formulate business strategies by identifying the internal and external factors. To this end, this study employed IFE matrix, EFE matrix, IE matrix, SWOT matrix, and QSP matrix. In the IE matrix, Bite n Chat has a medium and strong external environmental condition so that it is in cell II, which is the position of growth and development. There are six alternative strategies produced by the SWOT matrix with strategic priorities, namely increasing more intensive online and offline promotional activities obtained from the results of the QSP matrix analysis.